The Dilemma of Boundaries Toward a New Concept of Catchment - Taniguchi, Makoto; Shiraiwa, Takayuki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
Water circulates continuously and seamlessly on Earth with little regard for the boundaries we draw. There are natural boundaries as between land and ocean and surface and subsurface environments, as well as human or demographic boundaries between nations, cultures, and religions. Although considered necessary by societies, these human-created boundaries disrupt natural water circulation, leading to serious water-related environmental problems. The dilemma of how to manage water beyond our boundaries remains, and nations have different ways and means of controlling each form of water, whether as vapor, surface water, groundwater, or seawater. Recent findings on the interaction of water from land, oceans, and the atmosphere encourage researchers to undertake collaborative work that goes beyond the boundaries of each discipline, be it oceanography, surface and subsurface hydrology, climatology, or glaciology. Drawing on all these fields, the book focuses on two major boundaries: that between surface water and ground water, and that between terrestrial water and ocean water. This comprehensive work is of great value to experts in academia, international organizations, consulting firms, water resources, fisheries, and urban development planning agencies.
Keywords: Environmental sciences; Hydraulic engineering; Geography; Civil engineering; Environmental management; Environment; Environment, general; Geography (general).; Hydrogeology; Environmental Management; Civil Engineering